Local Mass Media and Multi-Stakeholders as Leading Sector in Disaster Communication at the Community Level - Aziz, Muhammad Hilmy; Prasetyo, Dwi; Putranto, Teguh Dwi; Arif, Lukman (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2025)
Indonesia is a disaster-prone country, with threats including earthquakes, tsunamis, volcanic eruptions, floods and landslides. Disaster communication at the community level means providing efforts to prevent and handle disaster events. This research aims to find the right instrument to improve digital literacy. It also describes how to implement disaster communication at the community level. The research method used to provide a new perspective related to this research is qualitative research, obtaining data using Focus Group Discussions (FGD). Research results can be used as a new standard for implementing disaster communication at the community level. First, local mass media is important in providing and optimizing literacy and community participation in disaster prevention or mitigation efforts. Local mass media are considered to have emotional and psychological closeness to the right way to approach the community based on local pride. Secondly, by collaborating with stakeholders, the community can optimize literacy with various perspectives and achievements obtained through various institutions.